Separation of Sn, Bi, Cu from Pb-free solder paste by ammonia leaching followed by hydrochloric acid leaching - Jeon, S.; Yoo, K.; Alorro, Richard (Elsevier, 2017)
A recycling process consisting of swelling, ammonia leaching and hydrochloric acid leaching was developed to recover Sn, Bi, Cu, and resin from Pb-free Sn-Bi-Cu solder paste. The resin was separated from metal powder by swelling the solder paste in methyl ethyl ketone at 30 °C, 200 rpm and 5% pulp density. The addition of distilled water precipitated the resin from methyl ethyl ketone. The recovered resin was confirmed to be epoxy resin by FT-IR analysis. Ammonia leaching followed by hydrochloric acid leaching was performed to separate Cu, Sn, Bi sequentially from metal powder. Copper was solubilized easily with leaching efficiency reaching 100% within 15 min under the following conditions: 5 M NH3 solution, 1 M (NH4)2CO3, 0.1 M CuCO3, 50 °C, and 1% pulp density. Tin and bismuth were recovered as leach residue in the ammonia leaching. Tin was selectively leached in 0.5 M HCl solution with 10,000 mg/L Sn4 + and 1% pulp density at 50 °C and 400 rpm, while Bi was not detected in the leach solution. The recycling process has successfully separated Sn, Cu, Bi and resin.